Pengaruh Desentralisasi Pendidikan terhadap Efektivitas Manajemen Di Sekolah Dasar - Salma, Salma Maulidia Putri; Alya Maulida Putri; Rusi Rusmiati Aliyyah (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the influence of educational decentralization on management effectiveness in elementary schools. Educational decentralization grants schools broader authority in resource management, decision-making, and educational program planning. This research employs a qualitative approach using a literature review method (library research). Data were collected from various sources such as books, national and international journals, scholarly articles, and relevant educational policy reports. The findings indicate that educational decentralization has a positive effect on the management effectiveness of elementary schools, particularly in the aspects of program planning, implementation, and evaluation. However, the implementation of this policy faces challenges such as capacity disparities, limitations in human resources, and suboptimal regulations. Therefore, comprehensive supporting policies and enhanced human resource capacity are needed so that decentralization can optimally contribute to improving the managerial performance of elementary schools.